I'm big now! - Simmons, Anthea (Andersen Press, 2017)
When you are big, you're not the baby anymore, but sometimes you want to do the baby things you used to do before! In this funny journey of discovery, one little girl decides to try out being a baby again, but discovers it is more fun being the big sister of the family